Use of proton-pump inhibitors is associated with depression: a population-based study. (13th September 2017) - Laudisio, Alice; Antonelli Incalzi, Raffaele; Gemma, Antonella; Giovannini, Silvia; Lo Monaco, Maria Rita; Vetrano, Davide L.; Padua, Luca; Bernabei, Roberto; Zuccalà, Giuseppe
ABSTRACT: Treatment with proton-pump inhibitors (PPIs) might be associated with neuropsychological side effects. We examined the association between use of PPIs and depressive symptoms in an elderly population. Mood was assessed by the 30-item Geriatric Depression Scale (GDS) in all 344 inhabitants of Tuscania (Italy) aged 75 years and over, without exclusion criteria; depression was defined by a GDS score ≥11. Use of PPIs was associated with a higher GDS score in linear regression analysis (B = 2.43; 95% CI = 0.49–4.38; p = 0.014) after adjusting; also, use of PPIs was associated with increased adjusted probability of depression in logistic regression (OR = 2.38; 95% CI = 1.02–5.58; p = 0.045). Higher PPIs dosages were associated with increased probability of depression (p for trend = 0.014). This association was independent of the diagnosis of peptic disease, as well as the use of antidepressant medications. No association was found between use of H2-blockers or antacids and the GDS score. Calculation of the population attributable risk indicated that 14% of depression cases could be avoided by withdrawal of PPIs. Use of PPIs might represent a frequent cause of depression in older populations; thus, mood should be routinely assessed in elderly patients on PPIs.